PERAN LINGKUNGAN DAN POLA ASUH ORANG TUA TERHADAP PEMBENTUKAN KARAKTER ANAK USIA DINI DI TK MIFTAHUL HUDA - Siti Qomariatul Munawaroh; Robiatul Adawiyah (SOCIAL EDU: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Character education in early childhood plays an important role in shaping their personality and future development. In the "golden age" phase, environmental factors, parenting patterns, and the role of schools have a big influence. Democratic parenting styles support positive characters such as independence, honesty and responsibility, while authoritarian or permissive parenting styles can have a negative impact on children's emotional and social aspects.  Schools that provide a conducive environment and positive social interaction also strengthen the moral values ​​applied at home. Research at Miftahul Huda Kindergarten examines the relationship between parenting styles, social environment, and the role of teachers in forming children's character. With a qualitative descriptive approach, the research results show that synergy between family, school and community is very important. A good collaboration between these three factors can create a generation that is not only academically intelligent, but also has strong character and high competitiveness. Therefore, character education must be the main focus in parenting and learning from an early age so that children grow into individuals who are responsible, have integrity and are ready to face future challenges.